2018
DOI: 10.1177/0963689718775628
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Serum Endostatin Levels in Diabetic Patients with Critical Limb Ischemia Treated by Autologous Cell Therapy or Percutaneous Transluminal Angioplasty

Abstract: The aim of this study was to compare the serum levels of the anti-angiogenic factor endostatin (S-endostatin) as a potential marker of vasculogenesis after autologous cell therapy (ACT) versus percutaneous transluminal angioplasty (PTA) in diabetic patients with critical limb ischemia (CLI). A total of 25 diabetic patients with CLI treated in our foot clinic during the period 2008–2014 with ACT generating potential vasculogenesis were consecutively included in the study; 14 diabetic patients with CLI who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
0
1
Order By: Relevance
“…Therefore we analyzed serum levels of angiogenic cytokines in our previous studies to prove that ACT caused no systemic vasculogenesis. We did not observe any increase in serum levels of proangiogeneic cytokines after ACT in our previous studies (32), on the other hand we demonstrated a significant increase in endogenous inhibitor of angiogenesis endostatin at 1 and 3 months after ACT, these results might explain the possible negative feedback reaction on the local vasculogenesis in the limb (33).…”
Section: Discussioncontrasting
confidence: 40%
“…Therefore we analyzed serum levels of angiogenic cytokines in our previous studies to prove that ACT caused no systemic vasculogenesis. We did not observe any increase in serum levels of proangiogeneic cytokines after ACT in our previous studies (32), on the other hand we demonstrated a significant increase in endogenous inhibitor of angiogenesis endostatin at 1 and 3 months after ACT, these results might explain the possible negative feedback reaction on the local vasculogenesis in the limb (33).…”
Section: Discussioncontrasting
confidence: 40%